1997
DOI: 10.1084/jem.185.4.791
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Breeding Environments on Generation and Activation of Autoreactive B-1 Cells in Anti-red Blood Cell Autoantibody Transgenic Mice

Abstract: In anti-red blood cell autoantibody transgenic (autoAb Tg) mice almost all B cells are deleted except for B-1 cells in the peritoneal cavity and the gut. About one-half of the auto Ab Tg mice suffer from autoimmune hemolytic anemia (AIHA) in the conventional condition. Oral administration of lipopolysaccharides activates B-1 cells and induces autoimmune symptoms in the Tg mice, suggesting that the autoimmune disease in anti-RBC autoAb Tg mice is triggered by infections. To examine the association of bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 18 publications
1
43
1
Order By: Relevance
“…Recently, it has been reported that hsp60 cross-reactive T cells mediate autoimmune pathology of the small intestine (29). In contrast to the above-mentioned studies (11)(12)(13)(14)(15)(16), in this study, we attribute reduced incidence and severity of, rather than induction of, AA to determinant mimicry.…”
Section: Discussioncontrasting
confidence: 51%
“…Recently, it has been reported that hsp60 cross-reactive T cells mediate autoimmune pathology of the small intestine (29). In contrast to the above-mentioned studies (11)(12)(13)(14)(15)(16), in this study, we attribute reduced incidence and severity of, rather than induction of, AA to determinant mimicry.…”
Section: Discussioncontrasting
confidence: 51%
“…Either the cells need a stimulus, which was provided only in vitro, or they are inhibited from further differentiation or from Ab production in the PerC by an unknown mechanism. Previous reports have suggested that the expansion and activation of PerC B-1 cells may be induced by two steps in autoantibody (anti-RBC Ab) transgenic mice; enteric bacteria increase the number of PerC B-1 cells, and pathogenic infection induces PerC B-1 cells to produce anti-RBC Abs (35,36). In those transgenic mice, oral administration of LPS could induce the production of autoantibodies from PerC B-1 cells, resulting in autoimmune symptoms (35).…”
Section: Discussionmentioning
confidence: 99%
“…In one anti-erythrocyte Ig transgenic model (Tg), expression of the IgM Tg directs a predominant B-1 cell phenotype (24). In this model, the development and maintenance of the autoreactive B-1 cells, which leads to spontaneous autoimmune hemolytic anemia, depends on the presence of enteric bacteria, suggesting a crossreaction of self-antigen with bacteria (25). It is possible that CM22-specific B cells are also naturally preserved in normal animals by self-antigen(s) and may be also maintained by similar epitopes on enteric bacteria.…”
Section: Discussionmentioning
confidence: 99%